2010
DOI: 10.1007/s10461-010-9744-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of HIV-Associated Neurocognitive Disorders Among Individuals Starting Antiretroviral Therapy in South Africa

Abstract: HIV-Associated Neurocognitive Disorders (HAND) exert an impact on everyday functions, including adherence. The prevalence of and risk factors for HAND in patients commencing anti-retroviral therapy in Southern Africa are unknown. Participants from primary care clinics in Cape Town, South Africa underwent detailed neuropsychological, neuropsychiatric, and neuromedical evaluation. Using the updated American Academy of Neurology (AAN) criteria, participants were classified into categories of HAND, and demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
121
3
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(138 citation statements)
references
References 29 publications
12
121
3
2
Order By: Relevance
“…Thus, whether such HIV-independent changes potentially affect MoCA scores is unclear and requires further study. In contrast to the current results, a study by Joska et al showed that being male rather than female was predictive of development of HIVassociated dementia (18). The disparity in findings can perhaps be explained by the fact that the female patients in the current study were significantly less educated than male patients.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Thus, whether such HIV-independent changes potentially affect MoCA scores is unclear and requires further study. In contrast to the current results, a study by Joska et al showed that being male rather than female was predictive of development of HIVassociated dementia (18). The disparity in findings can perhaps be explained by the fact that the female patients in the current study were significantly less educated than male patients.…”
Section: Discussioncontrasting
confidence: 99%
“…In other studies, HAND is also reported to be more prevalent in patients who were older and who had lower levels of education (17,18). However, MoCA was not used to assess neurocognitive disorders in non-HIV infected controls matched by age and educational level in the current study.…”
Section: Discussionmentioning
confidence: 75%
“…[11] Prevalences are higher among people accessing HIV care in sub-Saharan African countries with a high HIV seroprevalence. Prevalences of 42% for HAND and 25% for HAD were reported among individuals starting HAART in primary care centres in Cape Town, [12] with all study participants being in later stages of HIV infection. Cognitive disorder in HIV is particularly important in view of associations with poor adherence to HAART, faster disease progression and mortality.…”
Section: Prevalence Of Hiv-associated Dementiamentioning
confidence: 89%
“…Cognitive disorder in HIV is particularly important in view of associations with poor adherence to HAART, faster disease progression and mortality. [12] It is difficult to quantify the impact of numbers of people with dementia and of the age distribution of dementia cases in the region. Given an adult HIV seroprevalence of 15 -25% in southern African countries, it is conceivable that most patients with dementia in the region are likely to have HAD.…”
Section: Prevalence Of Hiv-associated Dementiamentioning
confidence: 99%
“…Higher prevalences have been seen among people accessing HIV care in high HIV seroprevalence sub-Saharan African countries (e.g. 42% with HAND and 25% with HIV-associated dementia in those starting HAART in primary care centres in Cape Town, South Africa) (33). Cognitive disorder in HIV is particularly important in view of associations with poor adherence to HAART, faster disease progression, and mortality (34).…”
Section: Reviewmentioning
confidence: 99%